Keputusan Investasi Dipengaruhi oleh Overconfidence, Financial Literacy, Risk Tolerance dan Risk Perception: (Studi Pada Nasabah PT. Phintraco Sekuritas Kantor Cabang Surabaya) (JIES : Journal of Islamic Economics Studies, 2023)
This study aims to examine and analyze the effect of overconfidence, financial literacy, risk tolerance, and risk perception on the investment decisions of PT. Phintraco Sekuritas Surabaya Branch Office. This study uses a quantitative approach and the type of associative research. The population in this study are customers who are members of PT. Phintraco Sekuritas Surabaya Branch Office. Samples were taken using the Slovin formula to obtain a total of 100 customers. Data analysis using SPSS 16.0. The results of this study indicate that (1) the overconfidence variable has a positive and significant effect on investment decisions, (2) the financial literacy variable has a positive and significant influence on investment decisions, (3) the risk tolerance variable has a negative and insignificant effect on investment decisions, (4) The variable of risk perception has a positive and significant influence on investment decisions, and (5) the variables of overconfidence, financial literacy, risk tolerance, and risk perception together have an influence on investment decisions.